2019
DOI: 10.1051/sicotj/2019021
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of persistent pain 6 months after arthroscopic subacromial decompression and/or acromioclavicular joint resection

Abstract: Purpose: The aims of this prospective study were to determine the prevalence of pain 6 months after arthroscopic subacromial decompression (ASD) and/or acromioclavicular joint resection (AC resection), to reveal causes of the pain, and to identify risk factors for persistent pain. Methods: Preoperatively, patients were tested for their endogenous capacity to modulate pain and completed questionnaires concerning psychological vulnerability. Patients with pain 6 months after surgery were examined by an experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Dragoo et al, 37 Levine et al 38 and Daluga and Dobozi 39 all found good outcomes including whether a direct or bursal approach was used. Brix et al 40 found persistent pain at 6 months after the operation in approximately one-third of participants, with associations to compensation cases and a propensity to anxiety amongst those suffering ongoing symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dragoo et al, 37 Levine et al 38 and Daluga and Dobozi 39 all found good outcomes including whether a direct or bursal approach was used. Brix et al 40 found persistent pain at 6 months after the operation in approximately one-third of participants, with associations to compensation cases and a propensity to anxiety amongst those suffering ongoing symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies also commented that participants who fared badly from surgery were worker compensation cases or those with predisposition to altered pain experience. Brix 40 with 6 months follow-up, found that 36% of participants had persistent pain with significant associations of unemployment, insurance/compensation and anxiety traits to a worse outcome. A number of other studies 41,44,45 found that work-related injury participants had a significantly decreased functional score post-surgery or worse outcomes.…”
Section: Rcrmentioning
confidence: 99%
“…The International Association for the Study of Pain defines PPSP in the International Classification of Diseases 11 as a chronic pain that develops or increases in intensity after a surgical procedure. 60 Other causes of pain, including preexisting pain conditions, have to be excluded, 5,8 and a careful clinical examination is sometimes needed to assess if there is remaining pathology with persistent preexisting pain (Fig. 1E).…”
Section: Persistent Presurgical Painmentioning
confidence: 99%
“…More than 300,000 rotator cuff repairs were performed in the United States between 2007 and 2016 [ 7 ], with postsurgical costs reaching US $34,249 per patient [ 8 ]. Moreover, a significant proportion of patients will experience persistent postsurgical pain after surgery, with 1 study finding a rate of 35.6% (95% CI 26.1%-45.8%) in 101 patients who underwent arthroscopic subacromial decompression or acromioclavicular joint resection [ 9 ]. These observations contrast with evidence showing that exercise-based rehabilitation yields similar reductions in disability and pain outcomes compared to rotator cuff repair [ 10 , 11 ] and subacromial decompression [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%